Physiological psychology - Schwartz, Marvin (Englewood Cliffs, New Jersey : Prentice-Hall, 1973)
This book is designed as an introduction to physiological psychology. It is meant to show, by example, how the physiological psychologists goes about his business, the kinds of questions he asks, and the way in which he conceptualizes problems.
1. Introduction -- 2. Genetics and behavior -- 3. Development of behavior -- 4. Sensory processes -- 5. Sleep and wakefulness -- 6. Attention and perception -- 7. Emotion -- 8. Reward and punishment with electrical stimulation of the brain -- 9. Hunger and thirst mechanisms -- 10. Sexual behavior and endocrine functions -- 11. Learning -- 12. Memory -- 13. Functional disorders.
Includes index.
Keywords: PSYCHOPHYSIOLOGY